SCREENING OF A PECTINOLYTIC FUNGAL STRAIN; Aspergillus foetidus MTCC 10367 FOR THE PRODUCTION OF MULTIPLE ENZYMES OF INDUSTRIAL IMPORTANCE - K.MEHRAJ PASHA; P.ANURADHA; D.SUBBA RAO (International Journal of Pharma and Bio Sciences, 2013)
Aspergillus foetidus MTCC 10367 associated with industrial fruit waste sample from Galla food processing industry, Chittoor District, Andhra Pradesh, was isolated and identified using standard microbiological method (serial dilution-spread plate technique). This fungal isolate was screened for hydrolytic and depolymerising multiple enzymes of industrial importance. Many enzymes such as Pectinases, Cellulases, Proteases, Phytases and Amylases produced by Aspergillus foetidus have relevant biotechnological applications in several industrial areas. This study revealed the ability of Aspergillus foetidus to produce varieties of hydrolytic enzymes and provides additional information to support future research about industrial potential of Aspergillus foetidus MTCC 10367.